Redescription of the Indian toadfish Perulibatrachus aquilonarius Greenfield (Teleostei: Batrachoididae) - Bineesh, K. K.; Greenfield, David W. (Zootaxa, 2011)
The second known specimen of Perulibatrachus aquilonarius from India is compared to the holotype and new information on fresh color is presented. A mitochondrial COI barcode also was generated for the specimen.